Al-I’jaz Al-Lughowi fii Qishati Maryam: Tafsir Surah Maryam Al-Ayat 25 - Haikal Mustafti (Universitas Darussalam Gontor, 2021)
This research is aimed to investigate the selection of words and sentences in the 25th verse from Surah Maryam (wa huzzy ilayki bi jidz’I al-nakhlati tusâqith ‘alaiki ruthaban janiyya) of the Qur'an. It seems to examine the hidden meaning of words and sentences in verses of the Qur’an in order to discover its linguistic miracle (al-I’jaz al-lughawi). This research used descriptive analytic method to investigate the meaning of the verse from the linguistic point of view. This study found two important points. The first, the verse mention that Maryam who is pregnant and giving birth was commanded by Allah to swing the date palm until the date falls and she can eat from it. To expressit, al-Qur’an articulates it with the word huzzy rather than ḥaraky. It was because that the verse wants to say that in order to achieve his goal, one should work hard. The second is that the Qur’an has similar view with that of the modern discoveries pertaining to the benefit of ruthab for pregnant women. Therefore, it is ruthab that has mentioned in this verse as the meal for Maryam who is pregnant. In addition, ruthab contains lots of sucrose which can make pregnant women easier to give birth beside the fact that it is also good for fetal development.